Balancing Safety and Comfort: A Novel Automatic Braking Control Method Using Seventh-Degree Polynomials - Fei Lai; Chaoqun Huang (Algorithms)
This study reinterprets the rear-end collision avoidance problem as a trajectory planning challenge, introducing an automatic braking control method based on seventh-degree polynomials. This approach effectively balances vehicle safety and comfort. Unlike traditional automatic braking control methods, e.g., time-to-collision or safety distance models, our method incorporates multiple constraints at both the initiation and conclusion of braking. Consequently, it significantly improves the braking comfort while ensuring collision avoidance; specifically, the braking deceleration changes smoothly rather than abruptly, greatly reducing the vehicle’s jerk value. In accordance with the Euro NCAP testing standards, three car-to-car rear (CCR) test scenarios, such as car-to-car rear stationary (CCRs), car-to-car rear moving (CCRm) and car-to-car rear braking (CCRb), were established within the CarSim environment. The proposed algorithm was rigorously evaluated through integrated simulations performed in CarSim and MATLAB/Simulink, demonstrating its effectiveness.